Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Di Lembaga Pemasyarakatan Kelas IIA Sumbawa - Winda Andi Apriani; Padmono Wibowo (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
This study aimed to examine the relationship between work motivation and employee performance. A simple linear regression analysis was conducted using data collected from employees in Lapas Kelas IIA Sumbawa. The results showed a weak positive correlation between the work motivation variable (X) and employee performance variable (Y). The regression analysis revealed that work motivation significantly influenced employee performance. The correlation coefficient between the two variables was 0.359, indicating a weak positive relationship. The analysis also indicated that 12.9% of the variation in employee performance could be explained by the work motivation variable, while the remaining 87.1% was influenced by other factors not considered in this study. This suggests the presence of other factors that also play a role in determining employee performance.